2016
DOI: 10.1177/0018726715610642
|View full text |Cite
|
Sign up to set email alerts
|

When and why do individuals craft their jobs? The role of individual motivation and work characteristics for job crafting

Abstract: As a proactive behavior, job crafting refers to changes in the task (cognitive, and behavioral) and social boundaries at work. This article focuses on antecedents of job crafting and the development and validation of a job crafting scale. In Study 1 (N = 466), an exploratory factor analysis with one half of the sample (n = 233) and a confirmatory factor analysis with the other half (n = 233) supported a three-dimensional structure of job crafting (task crafting, relational crafting and cognitive crafting), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
233
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(279 citation statements)
references
References 73 publications
14
233
0
18
Order By: Relevance
“…A third consequence of the divergent definitions of crafting is that it has been difficult to characterize how job crafting is similar to or different from other concepts, especially with other types of proactive behavior. Previous analyses (e.g., Niessen, Weseler, & Kostova, ; Tims & Bakker, ) have compared job crafting with some specific concepts (e.g., personal initiative, taking charge, and task revision), but how different types of job crafting fit into a broad proactivity scheme has rarely been discussed. For example, whether decreasing hindering demands (Tims et al, ) is proactive behavior is not clear.…”
Section: Job Crafting: Moving Toward Conceptual Claritymentioning
confidence: 99%
See 2 more Smart Citations
“…A third consequence of the divergent definitions of crafting is that it has been difficult to characterize how job crafting is similar to or different from other concepts, especially with other types of proactive behavior. Previous analyses (e.g., Niessen, Weseler, & Kostova, ; Tims & Bakker, ) have compared job crafting with some specific concepts (e.g., personal initiative, taking charge, and task revision), but how different types of job crafting fit into a broad proactivity scheme has rarely been discussed. For example, whether decreasing hindering demands (Tims et al, ) is proactive behavior is not clear.…”
Section: Job Crafting: Moving Toward Conceptual Claritymentioning
confidence: 99%
“…In other words, cognitive crafting and behavioral crafting are not conceptually interchangeable. Studies have indicated that they likely have different antecedents and outcomes (Niessen et al, ; Weseler & Niessen, ), and preliminary research has indicated that cognitive crafting has only moderate relationships with behavioral crafting (e.g., Niessen et al, ; Slemp & Vella‐Brodrick, , ). The latter relationships might occur because cognitive crafting and behavioral crafting are reciprocally related to each other.…”
Section: Job Crafting: a Proposed Hierarchical Structurementioning
confidence: 99%
See 1 more Smart Citation
“…They can make small adjustments to incorporate more of their passions, strengths, and motives into their work (Leana et al 2009, Niessen et al 2016. They can also form what psychoanalysts refer to as holding environments through creating greater connections to the places, people, routines, and purposes that sustain their work (Petriglieri et al 2016).…”
Section: Creating a More Positive New World Of Workmentioning
confidence: 99%
“…İş becerikliliği, bireylerin yaptıkları işte aktif bir rol oynadıkları, gelecek odaklı eylemler başlattıkları ve kişisel ihtiyaçlarına uygun koşullar yarattıkları proaktif bir davranıştır (Berg vd., 2010;Niessen, 2016). İş becerikliliğinde çalışanlar kişisel istek ve anlayışlarına göre ve kendi inisiyatifleri ile işlerinde fiziksel, bilişsel ve ilişkisel olarak davranış değişimleri gerçekleştirmektedir (Wrzesnieswski ve Dutton, 2001).…”
Section: İş Becerikliliği (Job Crafting)unclassified